Clinical Study Support by Long-Term Stability Studies of Alpha1-Proteinase Inhibitor and Urea in Relevant Biological Matrices - Andrea Engelmaier; Martin Zimmermann; Harald A. Butterweck; Alfred Weber (Pharmaceuticals)
Background/Objectives: According to recent guidelines, including the guideline on bioanalytical method validation issued by the European Medicine Agency, the stability of clinical analytes should be known. We summarize human α1-proteinase inhibitor (A1PI) and urea stability data in relevant matrices, as these analytes are usually measured in clinical A1PI studies. Methods: Stability samples with appropriate A1PI concentrations were prepared in a citrated human reference plasma pool and a matrix mimicking bronchoalveolar lavage (BAL) solution. These samples were kept at −20 °C and −60 °C for up to 24 months. A1PI protein was measured with a nephelometric method and an enzyme-linked immunosorbent assay using paired commercially available polyclonal antibodies. A1PI elastase inhibitory activity was determined with an elastase complex formation immunosorbent assay that combines A1PI complex formation with a solid phase-immobilized elastase and immunological detection of the formed A1PI-elastase complex and urea in samples kept at −20 °C only with an enzymatic assay. Results: Overall, the stability criterion (100 ± 20%) was met for the analytes A1PI protein and A1PI activity at both temperatures during storage of BAL-mimicking and plasma samples for 15 and 24 months, respectively; urea was stable in both matrices at −20 °C for 18 months. Plasma samples showed smaller drops in concentration over storage time than BAL-mimicking samples. As expected, the reduction of A1PI elastase inhibitory activity was more pronounced than that of A1PI protein. Interestingly, the analyte concentration did not significantly influence the results in either of the sample matrices. Conclusions: The data confirmed the appropriate stability of the three analytes in the matrices of citrated plasma and BAL-mimicking samples for at least up to 15 months.